The associations between caregivers’ psychosocial characteristics and caregivers’ depressive symptoms in stroke settings: a cohort study - Yen Sin Koh; Mythily Subramaniam; David Bruce Matchar; Song-Iee Hong; Gerald Choon-Huat Koh (BMC Psychology, 2022)
Abstract Background Studies have found that caregivers can influence stroke survivors’ outcomes, such as mortality. It is thus pertinent to identify significant factors associated with caregivers’ outcomes. The study objective was to examine the associations between caregivers’ psychosocial characteristics and caregivers’ depressive symptoms. Methods The analysis obtained three-month and one-year post-stroke data from the Singapore Stroke Study, which was collected from hospital settings. Caregivers’ depressive symptoms were assessed via the Center for Epidemiologic Studies Depression instrument. Psychosocial characteristics of caregivers included subjective burden (Zarit Burden Interview), quality of care-relationship (a modified 3-item scale from the University of Southern California Longitudinal Study of Three-Generation Families) and expressive social support (an 8-item scale from Pearlin et al.). Mixed effect Tobit regressions were used to examine the associations between these study variables. Results A total of 214 caregivers of stroke patients hospitalized were included in the final analysis. Most caregivers were Chinese women with secondary school education, unemployed and married to the patients. Caregivers' subjective burden was positively associated with their depressive symptoms (Partial regression coefficient: 0.18, 95% CI 0.11–0.24). Quality of care-relationship (Partial regression coefficient: − 0.35, 95% CI − 0.63 to − 0.06) and expressive social support (partial regression coefficient: − 0.28, 95% CI − 0.37 to − 0.19) were negatively associated with caregivers’ depressive symptoms. Caregivers’ depressive symptoms were higher at three-month post-stroke than one-year post-stroke (Partial regression coefficient: − 1.00, 95% CI − 1.80 to − 0.20). Conclusion The study identified subjective burden, quality of care-relationship and expressive social support as significantly associated with caregivers’ depressive symptoms. Caregivers’ communication skills may also play a role in reducing caregivers’ depressive symptoms.